2020
DOI: 10.1002/jbm4.10417
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in Vitamin D: A Statement From the Third International Conference

Abstract: The Third International Conference on Controversies in Vitamin D was held in Gubbio, Italy, September 10–13, 2019. The conference was held as a follow‐up to previous meetings held in 2017 and 2018 to address topics of controversy in vitamin D research. The specific topics were selected by the steering committee of the conference and based upon areas that remain controversial from the preceding conferences. Other topics were selected anew that reflect specific topics that have surfaced since the last internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
110
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 161 publications
(221 reference statements)
2
110
0
8
Order By: Relevance
“…Change to an indoor lifestyle and lack of food fortification with VD is likely the main reason accounting for the higher prevalence of low circulating VD levels in Italy and in other Mediterranean Countries vs many other central and North European Countries in which this is systemically the rule from several decades due to the low sun exposure leading to what is defined Scandinavian paradox [ 54 , 55 ]. In fact, a geographical overlap between high prevalence of hypovitaminosis D and elevated number and severity of COVID-19 cases has been observed [ 43 ].…”
Section: Review Of the Evidencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Change to an indoor lifestyle and lack of food fortification with VD is likely the main reason accounting for the higher prevalence of low circulating VD levels in Italy and in other Mediterranean Countries vs many other central and North European Countries in which this is systemically the rule from several decades due to the low sun exposure leading to what is defined Scandinavian paradox [ 54 , 55 ]. In fact, a geographical overlap between high prevalence of hypovitaminosis D and elevated number and severity of COVID-19 cases has been observed [ 43 ].…”
Section: Review Of the Evidencesmentioning
confidence: 99%
“…A few other studies reported an association between COVID-19 prevalence and related mortality with latitude and consequent sunlight availability [ 56 ]. Importantly, home confinement is the most used measure in order to prevent the spreading of SARS-CoV-2 infection but the drawback of this extremization of the above mentioned progressive changes in lifestyle may be the worsening in the VD status in already at huge risk patients particularly in heavily VD-deficient countries [ 54 ].…”
Section: Review Of the Evidencesmentioning
confidence: 99%
“…Recently, vitamin D deficiency has emerged as a public health concern due to its skeletal and extra-skeletal effects [ 18 ]. Children with SCD show a high prevalence of this condition, ranging from 56% to 96% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Vitamin D levels were reported to be lower in patients with autoimmune diseases than in healthy controls. [5][6][7]. Several animal studies have shown the role of vitamin D supplementation in controlling many autoimmune diseases such as arthritis and autoimmune encephalomyelitis.…”
Section: Introductionmentioning
confidence: 99%